Effects of direct oral anticoagulants vs. vitamin K antagonists on acute kidney injury in patients with atrial fibrillation: A systematic review - Ren, Chengfa; Zhao, Yudan; Liu, Dehui (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Background: Patients with atrial fibrillation (AF) are routinely prescribed oral anticoagulants to prevent thromboembolism. Concerns regarding the efficacy and safety of oral anticoagulants, such as vitamin K antagonists (VKA) and direct oral anticoagulants (DOACs), arise for patients with non-valvular atrial fibrillation (NVAF) because of their widespread use in clinical practice. Even though there have been a lot of studies on this topic, it is still not clear if DOAC users with NVAF have a lower risk of acute kidney injury (AKI) than warfarin users. Methods and results: Electronic searches were conducted in PubMed, Embase, and Cochrane. Randomized clinical trials and observational studies that reported the incidence rate, hazard ratio (HR), and its 95% confidence interval (95%CI) of AKI among patients using oral anticoagulants were selected. This systemic review included six observational studies and four randomized clinical trials (RCT). According to the overall results, DOACs outperformed warfarin since they are associated with a lower AKI risk. However, for NVAF patients with severe renal dysfunction, DOACs may not provide a reduced risk of AKI compared to warfarin. Conclusion: The overall results suggest that, except for edoxaban, patients can benefit from using DOACs with respect to a decreased AKI risk. However, among the population with severe renal dysfunction, the effect of DOACs may differ from that of those with normal renal function, more studies are required to reach a firm conclusion.